Death Zone Weather Extremes Mountaineers Have Experienced in Successful Ascents - Szymczak, Robert K.; Marosz, Michał; Grzywacz, Tomasz; Sawicka, Magdalena; Naczyk, Marta (Frontiers in Physiology, 2021)
(1) Background: Few data are available on mountaineers’ survival prospects in extreme weather above 8000 m (the Death Zone). We aimed to assess Death Zone weather extremes experienced in climbing-season ascents of Everest and K2, all winter ascents of 8000 m peaks (8K) in the Himalayas and Karakoram, environmental records of human survival, and weather extremes experienced with and without oxygen support. (2) Material and Methods: We analyzed 528 ascents of 8K peaks: 423 non-winter ascents without supplemental oxygen (Everest–210, K2–213), 76 ascents in winter without oxygen, and 29 in winter with oxygen. We assessed environmental conditions using the ERA5 dataset (1978–2021): barometric pressure (BP), temperature (Temp), wind speed (Wind), wind chill equivalent temperature (WCT), and facial frostbite time (FFT). (3) Results: The most extreme conditions that climbers have experienced with and without supplemental oxygen were: BP 320 hPA (winter Everest) vs 329 hPa (non-winter Everest); Temp –41 °C (winter Everest) vs –45 °C (winter Nanga Parbat); Wind 46 m·s−1 (winter Everest) vs 48 m·s−1 (winter Kangchenjunga). The most extreme combined conditions of BP ≤ 333 hPa, Temp ≤ − 30 °C, Wind ≥ 25 m·s−1, WCT ≤ − 54 °C and FFT ≤ 3 min were encountered in 14 ascents of Everest, two without oxygen (late autumn and winter) and 12 oxygen-supported in winter. The average extreme conditions experienced in ascents with and without oxygen were: BP 326 ± 3 hPA (winter Everest) vs 335 ± 2 hPa (non-winter Everest); Temp – 40 ± 0 °C (winter K2) vs – 38 ± 5 °C (winter low Karakoram 8K peaks); Wind 36 ± 7 m·s−1 (winter Everest) vs 41 ± 9 m·s−1 (winter high Himalayan 8K peaks). (4) Conclusions: 1. The most extreme combined environmental BP, Temp and Wind were experienced in winter and off-season ascents of Everest. 2. Mountaineers using supplemental oxygen endured more extreme conditions than climbers without oxygen. 3. Climbing-season weather extremes in the Death Zone were more severe on Everest than on K2. 4. Extreme wind speed characterized winter ascents of Himalayan peaks, but severely low temperatures marked winter climbs in Karakoram.